FERTILIZING ON THE BASIS OF THE COMBINED PLOW ROTOR - Бендера, І. М.; Василинич, М. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Mechanical cultivation is an important technological process in agriculture, connected with deep loosening of soil formation, seam turnover, earnings of root and vegetable residues and pre-fertilizing. The study considers the promising tendency of combining some agricultural operations into one technological process, if the set of the latter is not contrary to the technology of crops growing. The construction of combined plow which provides the fulfilment of deep plowing with ploughsharing racked working bodies, active layer crumbling with vertical rotors and mineral fertilizing (blending) at the whole depth of topsoil was designed on the basis of State Agrarian and Engineering University in Podilya Study Center. The analysis of the fertilizing with the help of the internal cavity of the rotor, where the working elements are blade holders is given in the study. The method of the power analysis of fertilizing particles movement on the surface of the blades was used in the article. The conditions of motion, rotation rate, spatial position of the blades were defined in the study.